Farm injury hospitalisations in New South Wales (2010 to 2014). (16th July 2017) - Lower, Tony; Mitchell, Rebecca J.
Abstract: Objective: To examine gender differences in the characteristics, treatment costs and health outcomes of farm injuries resulting in hospitalisation of New South Wales (NSW) residents. Method: A population‐based study of individuals injured on a farm and admitted to hospital using linked hospital admission and mortality records from 1 January 2010 to 30 June 2014 in NSW. Health outcomes, including injury severity, hospital length of stay (LOS), 28‐day readmission and 30‐day mortality were examined by gender. Results: A total of 6, 270 hospitalisations were identified, with males having a higher proportion of work‐related injuries and injuries involving motorbikes compared to females. Females had a higher proportion of equestrian‐related injuries. There were no differences in injury severity, with around 20% serious injuries, in mean LOS or 28‐day hospital re‐admission. Treatment costs totalled 42.7 million, with males accounting for just under 80% of the total. Conclusions: There are some gender differences in the characteristics of farm injury‐related hospitalisations. Farm injury imposes modest, but nonetheless relatively considerable, financial costs on hospital services in NSW. Implications for public health: Continued efforts to ameliorate these injuries in a farm environment, which are mainly preventable, will have personal and societal benefits.